Antioxidant activity of lidocaine, bupivacaine, and ropivacaine in aqueous and lipophilic environments: an experimental and computational study - Kavčič, H.; Jug, U.; Mavri, J.; Umek, N. (Frontiers in Chemistry, 2023)
Introduction: Local anesthetics are widely recognized pharmaceutical compounds with various clinical effects. Recent research indicates that they positively impact the antioxidant system and they may function as free radical scavengers. We hypothesize that their scavenging activity is influenced by the lipophilicity of the environment. Methods: We assessed the free radical scavenging capacity of three local anesthetics (lidocaine, bupivacaine, and ropivacaine) using ABTS, DPPH, and FRAP antioxidant assays. We also employed quantum chemistry methods to find the most probable reaction mechanism. The experiments were conducted in an aqueous environment simulating extracellular fluid or cytosol, and in a lipophilic environment (n-octanol) simulating cellular membranes or myelin sheets. Results: All local anesthetics demonstrated ABTS˙+ radical scavenging activity, with lidocaine being the most effective. Compared to Vitamin C, lidocaine exhibited a 200-fold higher half-maximal inhibitory concentration. The most thermodynamically favorable and only possible reaction mechanism involved hydrogen atom transfer between the free radical and the -C-H vicinal to the carbonyl group. We found that the antioxidant activity of all tested local anesthetics was negligible in lipophilic environments, which was further confirmed by quantum chemical calculations. Conclusion: Local anesthetics exhibit modest free radical scavenging activity in aqueous environments, with lidocaine demonstrating the highest activity. However, their antioxidant activity in lipophilic environments, such as cellular membranes, myelin sheets, and adipose tissue, appears to be negligible. Our results thus show that free radical scavenging activity is influenced by the lipophilicity of the environment.